Anne of Avonlea. - Montgomery, L. M. (Lucy Maud), 1874-1942 (First Avenue Classics Ser., 2016)
It has been five years since Anne Shirley first came to the Cuthbert farm on Prince Edward Island, and she is just as full of dreams and schemes at sixteen as she was at eleven. Anne has started teaching at the Avonlea School, where she finds a kindred spirit in Paul Irving, a young student who shares her imagination and whimsy. Anne and her friends attempt to reconcile Paul's father and their friend Miss Lavendar Lewis, who were once childhood sweethearts. Anne may be older, but she has the same knack for getting into trouble and charming everyone she meets. This coming of age story, first published in 1909, is the sequel to Canadian author Lucy Maud Montgomery's Anne of Green Gables.